2009
DOI: 10.2119/molmed.2009.00097
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition Receptor-Dependent Mechanisms of Acute Lung Injury

Abstract: Acute lung injury (ALI) that clinically manifests as acute respiratory distress syndrome is caused by an uncontrolled systemic inflammatory response resulting from clinical events including sepsis, major surgery and trauma. Innate immunity activation plays a central role in the development of ALI. Innate immunity is activated through families of related pattern recognition receptors (PRRs), which recognize conserved microbial motifs or pathogen-associated molecular patterns (PAMPs). Toll-like receptors were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 176 publications
(180 reference statements)
2
66
0
1
Order By: Relevance
“…Accumulating data in the literature suggest that patternrecognizing receptors play a significant role in acute inflammatory diseases [20,21]. In the present study, we observed that pancreatitis-associated amylase release, neutrophil recruitment and tissue damage were greatly decreased in animals lacking TLR4 whereas animals lacking TLR2 were no different from wild-type animals.…”
Section: Discussionsupporting
confidence: 44%
“…Accumulating data in the literature suggest that patternrecognizing receptors play a significant role in acute inflammatory diseases [20,21]. In the present study, we observed that pancreatitis-associated amylase release, neutrophil recruitment and tissue damage were greatly decreased in animals lacking TLR4 whereas animals lacking TLR2 were no different from wild-type animals.…”
Section: Discussionsupporting
confidence: 44%
“…Frequently, SIRS leads to dysfunction of multiple organs, including renal failure and acute lung injury. It has become clear that the innate immune system and its PRRs are the main players in the molecular pathway that leads to SIRS associated with trauma [21]. Indeed, it has been shown that several DAMPs, such as HMGB1 and S100 protein, are released into the bloodstream after severe trauma, and these DAMPs have been linked to the development of organ failure after trauma [22,23].…”
Section: Mitochondrial Dna Induces An Inflammatory Response To Injurymentioning
confidence: 99%
“…TLRs are abundantly expressed in macrophages and play an important role in Gram-negative sepsis or artificial LPS exposure to trigger the innate immune system [33, 34]. Specifically, TLR4 is essential for the opsonization of LPS, a physiologic membrane-bound component of the outer membrane of Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%